Facile Access to Fluoroaromatic Molecules by Transition‐Metal‐Free C–F Bond Cleavage of Polyfluoroarenes: An Efficient, Green, and Sustainable Protocol. Issue 2 (1st February 2016) - Liu, Cuibo; Zhang, Bin
Abstract: The creation of new bonds via C–F bond cleavage of polyfluoroarenes has proven to be an important and powerful tool in synthetic chemistry. Using such a strategy, a myriad of valuable partially fluoroaromatic molecules and building blocks can be obtained. The transition‐metal‐free nucleophilic aromatic substitution (SN Ar) strategy has aroused the continuing interest of researchers due to its simple, mild, economical, and environmentally benign characteristics, which have been successfully applied to C–F bond functionalizations. In this account, we present a summary of the recent investigations of polyfluoroarenes involving SN Ar reactions and discuss some of our recent endeavors in the construction of partially fluoroaromatic molecules. Through this strategy, many new bonds including C–C, C–N, C–O, C–S, and C–H bonds can be created. Additionally, brief discussions on the transformation mechanisms are also provided. Finally, we discuss the existing limitations of the SN Ar reactions of polyfluoroarenes as well as our perspective on the future development of this chemistry. Abstract : Cleavage of C–F bonds in polyfluoroarenes is an important and powerful tool in synthetic chemistry. The transition‐metal‐free nucleophilic aromatic substitution (SN Ar) is simple, mild, economical, and environmentally benign, and its application toward C–F bond functionalization is reviewed here. The use of the SN Ar strategy for the creation of C–C, C–N, C–O, C–S, and C–H bonds in pharmaceutical building blocks and materials molecules is discussed, alongside its mechanistic pathways and limitations and perspectives on the future development of this chemistry.